3D sedimentary architecture showing the inception of an Ice Age - H. Løseth (Nature Portfolio, 2020)
Northeast Atlantic climate shifted into the Quaternary Ice Age around 2.6 Myr ago. Here, the authors use 3D seismic data from the northern North Sea to document detailed changes in continental-margin sedimentary architecture spanning the transition from a fluvially dominated environment to an icehouse world.